ANALYSIS OF OBSTACLES OF COMMUNITY RIGHTS TO ACCELERATE BLUE ECONOMIC DEVELOPMENT OF THE EAST FAKFAK DISTRICT COMMUNITY - Titis Istiqomah (Jurnal Scientia, 2023)
East Fakfak District is one of the disadvantaged areas in Fakfak district. The potential for abundant coastal and marine resources does not necessarily guarantee the progress of blue economic development due to several obstacles to customary rights. The research aims to find a strategy to accelerate blue economy development by involving the active role of customary rights holders as part of business decision making; implemented during 2023. Descriptive approach method using qualitative analysis tools with a combination of weighting. Data was obtained from a combination of field observations, in-depth interviews with the community, and the opinions of competent experts using a triangulation approach. The results of the research show that motivation and integrity with traditional etiquette have opened up the understanding of customary rights holders and the community regarding the importance of investing in the East Fakfak district. This will increase ecotourism activities, sea transportation and renewable energy which we have been trying to realize so far towards accelerating community economic development.